2017
DOI: 10.1016/j.ijscr.2017.07.058
|View full text |Cite
|
Sign up to set email alerts
|

Chylopericardium following thoracoscopic resection of a mediastinal cyst: A case report

Abstract: HighlightsA resection of a thoracic duct cyst in the right upper mediastinum resulted in post-operative chylopericardium.Chylous complications in thoracic duct cysts are frequent when intraoperative diagnosis is not reached, such as in cases with anomalous cyst location.A review on post-surgical chylopericardium is performed, which will provide information for future management of this rare complication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…Gopalsamy et al (11) reported that the inhibition of IL-1β and IL-6 expression effectively inhibits the pain stress response. In the study of different operation methods for mediastinal tumor resection, Uchida et al (23) and Kamata et al (24) found that VATS is the first choice for tumor resection. In the present study, a judgement of pain stress indicators was added in the confirmation of results, which enhanced the real-time control of operation.…”
Section: Discussionmentioning
confidence: 99%
“…Gopalsamy et al (11) reported that the inhibition of IL-1β and IL-6 expression effectively inhibits the pain stress response. In the study of different operation methods for mediastinal tumor resection, Uchida et al (23) and Kamata et al (24) found that VATS is the first choice for tumor resection. In the present study, a judgement of pain stress indicators was added in the confirmation of results, which enhanced the real-time control of operation.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of these respiratory complications is not only clinical but also economical given that they result in longer hospital stay ( 7 , 10 , 11 ). Risk factors for developing postoperative pulmonary complications following thoracic surgery include age, pulmonary function tests, cardiovascular co morbidity, current smoking and chronic obstructive pulmonary disease ( 10 - 12 ).…”
Section: Postoperative Respiratory Complicationsmentioning
confidence: 99%
“…Arrhythmias are reported after any thoracic surgery ( 3 , 4 , 7 , 10 , 13 ). Risk factors for arrhythmias include: cardiovascular co-morbidities, postural change, anesthetic agents, extensive dissection, intraoperative bleeding, previous thoracic irradiation and age ( 2 , 3 , 14 ).…”
Section: Cardiac Complicationsmentioning
confidence: 99%
See 2 more Smart Citations